Technical Note: Impact of region of interest size and location in Gafchromic film dosimetry. Issue 5 (18th April 2018) - Gholizadeh Sendani, Neda; Karimian, Alireza; Ferreira, Clara; Alaei, Parham
Abstract : Purpose: To evaluate dependence of measured dose on size and location of region of interest (ROI) in Gafchromic EBT3 film dosimetry. Methods: Gafchromic EBT3 films were irradiated perpendicularly using the 6MV beam from a linear accelerator at 10 cm depth (100 cm SSD) of a 30 × 30 × 20 cm 3 solid water phantom for a range of field sizes of 6 × 6 to 100 × 100 mm 2 . ImageJ software was used for reading pieces of film. The appropriate location of ROIs in scanned films was found by two methods. First, the ROI was visually placed at the center of image. Second, the profile of pixel value versus distance was plotted and the center of profile was used for drawing ROI. Each scanned film was read using both methods and for three ROI sizes (1, 2, and 4 mm). A plastic scintillator, Exradin W1, was used as the reference dosimeter. Results: Comparing the three ROI sizes using both methods showed that there was less than 2% difference from reference in output factor measurements for field sizes larger or equal to 10 × 10 mm 2 . The percentage differences were increased in field sizes smaller than 10 × 10 mm 2 and for ROI size of 4 × 4 mm 2 for both centered‐ROI and profiled‐ROI methods. The mean percentage differences from reference measurements, for field sizes of 100 × 100 to 20 × 20 mm 2, were smaller than 1% in both methods of ROI positioning. For field sizes of 15 × 15 and 10 × 10 mm 2, the smaller mean percentage differences were observed in profiled‐ROI (4 × 4 mm 2 ) and centered‐ROI (4 × 4 mm 2 ). For the field sizes of 8 × 8 and 6 × 6 mm 2, the profiled‐ROI (2 × 2 mm 2 ) had smallest mean percentage difference, which was 0.88%. Conclusion: The ROI size of 4 × 4 mm 2 is appropriate for dose measurements in field sizes of 100 × 100 mm 2 to 10 × 10 mm 2, regardless of the method of finding location of ROI. In field sizes smaller than 10 × 10 mm 2, finding location of the ROI by profile of pixel values increases the accuracy of measurement, and ROI size of 2 × 2 mm 2 has the smallest difference from the reference dose measurements.